The corporate financial effects of corporate social responsibility, as executed by, and impacted upon, Prime Bank Limited, Bangladesh - Cawood, Benjamin Winters (2015)
Corporate Social Responsibility (CSR) is being implemented in the corporate world at an ever increasing rate, benefitting societies around the world. Several theories have been proposed that contend that the corporations who are implementing CSR programs also benefit financially, making the relationship a symbiotic one. This paper analyzes the financial health of Prime Bank Limited, Bangladesh, (PBL) over a period of a decade in order to determine if PBL has indeed benefited financially from implementing its CSR program. The analysis focuses on examining PBL’s internal and external financial indicators over an extended period of time to determine what the net effect, if any, that the CSR program has had on them. This analysis concludes that the evidence does not support the claim of a causal relationship between CSR spending and positive effects upon PBL, as measured by PBL’s financial indicators.